(untitled) (Historia, 2021)
English This article analyses the normative dimensions of urban administration in South Africa in the 1950s, focusing particularly on the administration of urban blacks. It argues that an “ethical life” or ethos of patriarchalism prevailed, and that this formed the normative backdrop for widespread paternalism on the part of white officials. However, the ethos of patriarchalism was fraught with ambiguities, because the political future of urban blacks within “white cities” remained unclear. Some officials believed that urban blacks would remain permanently subordinate in the cities, while others believed that they would eventually achieve full status as equals within a modern civil society. This ambiguity bedevilled the design of urban policies, and led to constant confusion and debates about appropriate urban management systems. Afrikaans Patriargisme en Paternalisme in Suid-Afrikaanse “Naturelle-Administrasie” in die 1950’s Hierdie artikel bespreek die normatiewe aspekte van stedelike administrasie in Suid-Afrika in die 1950’s, met spesifieke verwysing na die administrasie van die stedelike swart bevolking. Dit bewys dat ŉ patriargale etiek bestaan het, en dat dit die normatiewe konteks vir blanke amptenare se paternalistiese houding was. Nogtans was die patriargale etos baie dubbelsinnig, omdat die politieke toekoms van stedelike swartes onduidelik was. Sekere amptenare het geglo dat stedelike swartes altyd onderdanig sal bly, terwyl ander geglo het dat swartes mettertyd gelyke politieke status binne ŉ moderne samelewing sou bereik. Hierdie teenstrydighede was problematies vir die ontwerp van stedelike beleid, en het gelei tot voortdurende verwarring en debattering oor die mees geskikte administratiewe stelsels.